Signature Provisions in the Amended Indian Information Technology Act 2000: Legislative Chaos. (September 2014) - Shah, Hemali; Srivastava, Aashish
The Indian Parliament enacted the Information Technology Act (ITA) in 2000 to provide legal recognition to e-commerce and e-governance. The ITA, however, was heavily criticized for being technology-specific in nature and was therefore amended in 2008 to give it a technology-neutral status. The aim of this paper is to examine critically the provisions related to electronic signatures in the amended legislation by comparing them with the United Nations Commission on International Trade Law (UNCITRAL) model laws, the European Union Directive on Electronic Signatures and other electronic signatures legislation across the world. The paper concludes that, despite the amendments, the ITA is still a weak legislation, complex to understand, ambiguous and fails to address many aspects of electronic signatures usage. It is also an over-regulated legislation compared with similar legislation in other developing countries such as China and developed countries such as Australia, the UK and Singapore. Finally, the authors provide some recommendations, which can potentially address the shortcomings of the ITA.